2015
DOI: 10.1139/cjc-2014-0600
|View full text |Cite
|
Sign up to set email alerts
|

DNA-templated fluorescent gold nanoclusters reduced by Good’s buffer: from blue-emitting seeds to red and near infrared emitters

Abstract: DNA templated fluorescent gold nanoclusters (AuNCs) have been recently prepared, showing higher photostability than the silver counterpart. In this work, we examined the effect of pH, DNA length, sequence and reducing agent. Citrate, HEPES and MES produce blue emitters, glucose and NaBH4 cannot produce fluorescent AuNCs, while ascorbate shows blue emission even in the absence of DNA. This is the first report of using Good's buffer for making fluorescent AuNCs.Dimethylamine borane (DMAB) produces red emitter. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 49 publications
2
18
0
Order By: Relevance
“…Oligonucleotides are not only genetic material in biology, but also useful tools in chemistry, such as used as a template to prepare nano-materials [16][17][18] used as an element to engineer nano-probe and used as the "chemistry antibody" to recognize targets (aptamer) and so on. [19][20][21] The thymine (T) base of oligonucleotide specic binding with Hg 2+ to form "T-Hg 2+ -T" complex, and since it was reported, 22 many sensors for detection of Hg 2+ have been developed based on it.…”
Section: Introductionmentioning
confidence: 99%
“…Oligonucleotides are not only genetic material in biology, but also useful tools in chemistry, such as used as a template to prepare nano-materials [16][17][18] used as an element to engineer nano-probe and used as the "chemistry antibody" to recognize targets (aptamer) and so on. [19][20][21] The thymine (T) base of oligonucleotide specic binding with Hg 2+ to form "T-Hg 2+ -T" complex, and since it was reported, 22 many sensors for detection of Hg 2+ have been developed based on it.…”
Section: Introductionmentioning
confidence: 99%
“…40 For example, trivalent lanthanide ions react with nucleotides to form NPs. 24 Adenosine and Au 3+ form luminescent NPs after citrate reduction and UV light exposure, 41,42 while non-fluorescent materials were obtained by mixing adenine and Au 3+ . 36 We recently found that Zn 2+ coordinates with adenosine monophosphate (AMP) to form hydrogels.…”
Section: Resultsmentioning
confidence: 99%
“…Recently also DNA has been employed as templating agent for GNCs synthesis, [77][78][79][80] leading to the production of highly luminescent clusters with different emission colors [81] and controlled number of atoms. [82] Despite the use of proteins and DNA guarantees excellent biocompatibility, also dendrimers and other polymers were used as templating agent to achieve different structure and surface functionalization.…”
Section: Macromolecules Templated Synthesismentioning
confidence: 99%